Genome‐wide association studies of 27 accelerometry‐derived physical activity measurements identified novel loci and genetic mechanisms. Issue 2 (18th January 2022) - Qi, Guanghao; Dutta, Diptavo; Leroux, Andrew; Ray, Debashree; Muschelli, John; Crainiceanu, Ciprian; Chatterjee, Nilanjan
Abstract: Physical inactivity (PA) is an important risk factor for a wide range of diseases. Previous genome‐wide association studies (GWAS), based on self‐reported data or a small number of phenotypes derived from accelerometry, have identified a limited number of genetic loci associated with habitual PA and provided evidence for involvement of central nervous system in mediating genetic effects. In this study, we derived 27 PA phenotypes from wrist accelerometry data obtained from 88, 411 UK Biobank study participants. Single‐variant association analysis based on mixed‐effects models and transcriptome‐wide association studies (TWAS) together identified 5 novel loci that were not detected by previous studies of PA, sleep duration and self‐reported chronotype. For both novel and previously known loci, we discovered associations with novel phenotypes including active‐to‐sedentary transition probability, light‐intensity PA, activity during different times of the day and proxy phenotypes to sleep and circadian patterns. Follow‐up studies including TWAS, colocalization, tissue‐specific heritability enrichment, gene‐set enrichment and genetic correlation analyses indicated the role of the blood and immune system in modulating the genetic effects and a secondary role of the digestive and endocrine systems. Our findings provided important insights into the genetic architecture of PA and its underlying mechanisms.